Systematics and biogeography of shrews (soricomorpha: soricidae) in peninsular Malaysia / Hasmahzaiti Omar - Omar, Hasmahzaiti (2012)
total of 122 samples were examined in this study were trapped by using pitfall traps, except for Suncus murinus species, which was caught with a rat trap. The 14 skull characters of seven species measured from the past and present studies were subjected to principal component analysis. Although Crocidura negligens was never trapped in this study, earlier studies indicated that this species was distinct from other Crocidura species. Currently, Crocidura monticola are commonly found in Peninsular Malaysia and widely distributed in Sundaland. Previous studies indicated that Crocidura fuliginosa was dominant species in this region. Meanwhile, the smallest shrew Suncus malayanus formerly known as Suncus etruscus proved distinct morphologically from C. monticola. Finally, in this study I provide identification keys for shrew species, morphological measurements and skull drawings that may help in identification of Malay peninsula shrews for future studies. Small crocidurinae shrews (weight < 8g) from Southeast Asia have been poorly studied to date, mainly because of the difficulty to catch them and the concomitant paucity of reference specimens available in museums. Hence their systematics is still debated, and most small Crocidura shrews from Sundaland are assigned to the monticola species complex. Morphometric analyses based on 14 skull measurements showed that these shrews tend to be larger with increasing altitude, but showed otherwise no consistent variation. When compared to museum specimens of the monticola species complex sampled in the Sundaland (total: 77 specimens), the Malay shrews tend also to be larger than those living on Kalimantan and Sumatra. All are, however, morphologically distinct from the other species, C. maxi, found in eastern Java and on the Lesser Sundas. Molecular analyses of a subset of these small shrews based iv on a mitochondrial (cytochrome b) and a nuclear gene (Apolipoprotein B) suggest that samples from the central region of Peninsular Malaysia (Bukit Rengit and Ulu Gombak) differ genetically from other Malaysian populations (by about 7% K2P distance at the cyt b gene) and are more closely related to some samples from Sumatra and Borneo. These differences did not correlate with the altitudinal variation evidenced from the morphological analysis. Reference sequences from the terra typica of monticola and maxi (both species were originally described from Java) are however needed to determine if these unexpected genetic differences warrant additional taxonomic subdivision within the Sundaland. A portion of the mitochondrial cytochrome b gene was used to investigate the phylogenetic relationships of Suncus pygmy shrews and to help clarify the taxonomic status of the Malayan Pygmy Shrew (S. malayanus) and the Malagasy Pygmy Shrew (S. madagascariensis). Phylogenetic reconstructions were performed using neighbourjoining and Bayesian analysis methods and revealed that S. malayanus is related to, but distinct from S. etruscus. The K2P-corrected genetic distance among the Malaysian taxon and other pygmy shrews for the cytochrome b gene was between 6.1 and 8.5%, supporting recognition that S. malayanus represents a distinct species from the geographically widespread S. etruscus species complex. A close (1.5% K2P distance) sister-group relationship was revealed between S. etruscus from Sri Lanka and S. madagascariensis from Madagascar, which has been considered an island endemic, and suggests that these animals are not specifically distinct. The Malagasy population of this shrew most probably was translocated to the island by human intervention, with the lineage originating from Southeast Asia or the Indian subcontinent.